Tyrosine kinase inhibitor (STI-571) in the treatment of Ph positive chronic myelocytic leukaemia and acute lymphoblastic leukaemia - Wiktor Jędrzejczak, Wiesław (Contemporary Oncology/Współczesna Onkologia, 2001)
2-Phenylaminopyrimidine derivative, that was found to be a selective tyrosine kinase inhibitor and became known under abbreviated name STI-571 has reached the stage of clinical practice and began to be used in interferon-resistant cases of chronic myelocytic leukaemia, and (although with lesser success) in Philadelphia (Ph) chromosome positive acute leukaemias. Interesting is also its application in stromal gastrointestinal tumors. STI-571 is the first non-cytostatic drug with a specific antineoplastic activity. Currently, it is a novel therapeutic option for patients who ceased to respond to earlier treatment. It is difficult at present to predict, how all this will change the current treatment guidelines and the role of other methods. It is already known, that similarly to other drugs neoplastic cells develop resistance to STI-571. Virtually nothing is known about long range effects. On other hand, the initial reports on advantages of combination of STI-571 with cytostatics, interferons and other tyrosine kinase inhibitors were already published. They may open entirely new therapeutic opportunities.